2022
DOI: 10.1097/md.0000000000031807
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of proton pump inhibitors versus vonoprazan in treatment of erosive esophagitis: A PRISMA-compliant systematic review and network meta-analysis

Abstract: Background: Proton-pump inhibitors (PPIs) and vonoprazan are recommended as first-line therapies for erosive esophagitis (EE). However, it is uncertain how the magnitude of efficacy and safety of first-line therapy, the choice of individual PPIs or vonoprazan in the treatment of EE remains controversial. This study aimed to evaluate the efficacy and safety of vonoprazan and PPIs in healing esophageal mucosal injury in patients with EE.Methods: Relevant databases were searched to collect randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…There was no significant difference in the rate of adverse events among all PPIs, vonoprazan, and placebo. The study concluded that ilaprazole, esomeprazole, and vonoprazan were more effective in healing mucosal erosion, but no significant differences were observed in terms of safety among all interventions 22 . This is in disagreement to our study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…There was no significant difference in the rate of adverse events among all PPIs, vonoprazan, and placebo. The study concluded that ilaprazole, esomeprazole, and vonoprazan were more effective in healing mucosal erosion, but no significant differences were observed in terms of safety among all interventions 22 . This is in disagreement to our study.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, Yang et al . 22 conducted a network meta-analysis to identify first-line therapies for erosive esophagitis and found that all PPIs and vonoprazan significantly improved endoscopic cure rates compared to placebo. Ilaprazole was ranked as the most effective followed by esomeprazole, vonoprazan, pantoprazole, lansoprazole, omeprazole, rabeprazole, and placebo based on the surface under the cumulative ranking curve.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, vonoprazan, a new potassium-competitive acid blocker, has an elimination half-life of up to 9 h (Sakurai et al, 2015). Notably, both ilaprazole and vonoprazan promote the healing of gastric mucosa by inhibiting gastric acids and maintaining a pH greater than 4 for protracted durations (Yang et al, 2022). Taken together, the combination of strong gastric acid suppression and the maintenance of a high intra-gastric pH are likely contributing factors to the high eradication rate observed with ilaprazole-based dual therapy.…”
Section: Compliance and Adverse Eventsmentioning
confidence: 99%
“…Previous meta-analyses have examined the non-inferiority of P-CABs compared with lansoprazole in the treatment of H. pylori infection ( Jung, Kim, and Park, 2017 ), artificial ulcers after endoscopic submucosal dissection (ESD) ( Liu et al, 2019 ) and esophagitis (including reflux and erosive esophagitis) ( Miwa et al, 2019 ; Yang et al, 2022 ). Based on clinical and evidence-based medicine outcomes, P-CABs are currently recommended in guidelines for the management of two acid-related diseases: esophagitis and H. pylori eradication therapy ( Jung et al, 2021 ; Iwakiri et al, 2022 ; Zhou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%